Alquimista: uma Ferramenta para Desenvolvimento Visual de Software Paralelo para Modelos de Programação baseados em Memória Compartilhada - Barros, Márcio de Oliveira; Aude, Júlio Salek (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 1997)
This paper presents Alquimista, a visual programming tool for parallel software development. Alquimista is based on multithreaded programming and uses shared memory for communication. It allows users to build complex programs based on primitive programming blocks. Alquimista works upon meta-schemes of parallel programming models and generates code in any model described with these meta-schemes. Alquimista is implemented in Java and is currently available on Solaris platform.